1999
DOI: 10.1161/01.str.30.3.606
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography and Doppler Sonography for Emergency Assessment in Acute Basilar Artery Ischemia

Abstract: Background and Purpose-Both Doppler sonography (DS) and spiral CT angiography (CTA) are noninvasive vascular assessment tools with a high potential for application in acute cerebral ischemia. The usefulness of CTA for vascular diagnosis in acute basilar artery (BA) ischemia has not yet been studied. Methods-We prospectively studied 19 patients (meanϮSD age, 58Ϯ11 years) with clinically suspected acute BA occlusion by DS and CTA. Prior extracranial and transcranial DS was performed in all but 1 patient, with DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 26 publications
2
56
1
Order By: Relevance
“…Similar results had been obtained previously by Ley-Pozo 29 and Camerlingo 30 in anterior circulation artery occlusions. In posterior circulation arteries, our results are in agreement with the reports by Brandt 31 and Tsivgoulis 32 who found that TCD had lower sensitivity but high specificity in the diagnosis of occlusive disease. This is probably related to the high frequency of morphological variants in the posterior circulation.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results had been obtained previously by Ley-Pozo 29 and Camerlingo 30 in anterior circulation artery occlusions. In posterior circulation arteries, our results are in agreement with the reports by Brandt 31 and Tsivgoulis 32 who found that TCD had lower sensitivity but high specificity in the diagnosis of occlusive disease. This is probably related to the high frequency of morphological variants in the posterior circulation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies comparing CTA with conventional angiography by Knauth et al 5 showed agreement in 11 of 11 patients (100%), by Brandt et al 6 When CTA is compared with all DSAs, both acute and subacute, agreement is still good (86%) despite the fact that subacute angiograms might differ from the acute CTA because of spontaneous recanalization or subsequent reocclusion. When CTA is compared with all possible follow-up testing (DSA, MRA, and brain imaging studies), there is overall confirmation of the CTA reading in 80% of cases.…”
Section: Discussionmentioning
confidence: 85%
“…CT angiography (CTA) is potentially useful for this purpose: previous studies evaluating CTA in acute stroke have demonstrated its feasibility and have shown good correlation with other vascular imaging modalities. [5][6][7][8] We sought to provide further data on the accuracy of CTA in acute stroke and to investigate its ability to predict clinical outcome.…”
mentioning
confidence: 99%
“…Although high-level evidence regarding the role of thrombolytic therapy in such cases is lacking, it is clear that early diagnosis is essential if direct or supportive measures are to be of benefit. 1 Computed tomography angiography (CTA) has been shown to be highly accurate in detecting acute basilar artery occlusion, 2,3 and other forms of advanced imaging, including MRI with perfusion imaging, have been used to assess the viability of tissue in patients with basilar artery occlusion. 4 Despite this, most community medical centers do not yet routinely perform advanced imaging in stroke patients, but rather continue to rely on unenhanced CT for their clinical decision-making.…”
mentioning
confidence: 99%